Increasing inflationary T‐cell responses following transient depletion of MCMV‐specific memory T cells. Issue 1 (17th November 2014) - Sims, Stuart; Klenerman, Paul
<x xml:space="preserve">Abstract</x> Murine CMV (MCMV) infection induces effector CD8+ T cells that continue to increase in frequency after acute infection ("inflation") and are stably maintained at a high frequency, with up to 20% of the CD8+ T‐cell compartment being specific for one epitope, although the flexibility and turnover of these populations is not fully defined. Here we report that effector/memory CD8+ T cells induced by MCMV can be paradoxically boosted following transient depletion of epitope specific CD8+ T cells. Treatment of MCMV‐infected mice with MHC‐Class I‐saporin tetramers led to partial (80–90%) depletion of epitope‐specific CD8+ T cells—rapidly followed by a rebound, leading to expansion and maintenance of up to 40% of total CD8+ T cells, with minimal changes in response to a control epitope (M45). These data indicate the tight balance between host and virus during persistent infection and the functional flexibility of the "inflated" CD8+ T cell responses during persistent infection.